2004
DOI: 10.1111/j.1365-2982.2004.00582.x
|View full text |Cite
|
Sign up to set email alerts
|

High interdigestive and postprandial motilin levels in patients with the irritable bowel syndrome

Abstract: Motilin shows cyclic variation with the different phases of the migrating motor complex (MMC). Altered motilin levels have been found in irritable bowel syndrome (IBS) patients, but in these studies motilin levels were analysed without the knowledge of the phases of MMC. We included 13 healthy controls (HC) and 24 patients with IBS [12 diarrhoea-predominant (IBS-D) and 12 constipation-predominant (IBS-C)]. We performed interdigestive and postprandial antroduodenojejunal manometry and blood samples for analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 45 publications
0
13
1
1
Order By: Relevance
“…The secretion of motilin is regulated by neuropsychic factors and affected by eating [37-40]. Zhang et al [39] Measured plasma motilin of 21 patients with STC and 33 heathly people in fasting and one hour postprandial, and found that fasting motilin of STC patients was lower than those healthy people, but the difference was not significant (p > 0.05), which is inconsistent with our study.…”
Section: Discussioncontrasting
confidence: 99%
“…The secretion of motilin is regulated by neuropsychic factors and affected by eating [37-40]. Zhang et al [39] Measured plasma motilin of 21 patients with STC and 33 heathly people in fasting and one hour postprandial, and found that fasting motilin of STC patients was lower than those healthy people, but the difference was not significant (p > 0.05), which is inconsistent with our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Serotonin and motilin have been altered in IBS patients. A study showed enhanced motilin in diarrhea-predominant patients,70 while another study showed increased motilin in diarrhea-predominant and constipation-predominant patients 71. Despite finding no difference of plasma ghrelin concentration, Sjolund et al29 reported that the ratio of acyl-ghrelin to total ghrelin decreases.…”
Section: Ghrelin In Functional Gi Disordersmentioning
confidence: 98%
“…Increased blood levels of motilin have been associated with lower bowel disorders rather than upper gut disorders. For example, increased blood levels of motilin have been reported in patients with diarrhoea-or constipation-predominant forms of irritable bowel syndrome (IBS; Simrén et al, 2005). In addition, increased release of motilin has been reported in IBS patients undergoing psychological stress (in which colonic motility was also increased; Fukudo and Suzuki, 1987) and in constipation-predominant IBS patients receiving an infusion of intraduodenal lipids (there was a tendency for motilin concentrations to be reduced in the diarrhoea-predominant group; Simrén et al, 2001).…”
Section: Functions Of Endogenous Motilinmentioning
confidence: 99%